Ex Vivo Lung Perfusion with β-Nicotinamide Adenine Dinucleotide (NAD+) Improves Ischemic Lung Function - Jonas Peter Ehrsam; Jin Chen; Hector Rodriguez Cetina Biefer; Isabelle Opitz; Stephan Arni; Ilhan Inci (MDPI AG, 2022)
Ischemia-reperfusion injury compromises short- and long-term outcomes after lung transplantation. The scarce existing data on NAD+ suggest effects on hypoxia-induced vasoconstriction, on reactive oxygen species and on tampering inflammation. We exposed rat lungs to 14 h of cold ischemic storage and perfused them in a rat ex vivo lung perfusion (EVLP) system for 4 h. A control group (n = 6) was compared to groups receiving 100 µM (n = 6) or 200 µM NAD+ (n = 6) in the preservation solution and groups receiving 200 µM (n = 4) or 2000 µM (n = 6) NAD+ every 30 min in the perfusate, starting at 1 h of EVLP. Compared to the control, significant effects were only achieved in the 2000 µM NAD+ group. During the 4 h of EVLP, we monitored higher vascular flow, lower mean pulmonary arterial pressure and increased oxygenation capacity. Tissue inflammation estimated with the myeloperoxidase assay was lower in the 2000 µM NAD+ group. We observed higher levels of anti-inflammatory IL-10, higher anti-inflammatory IL-6/IL-10 ratios and lower levels of pro-inflammatory IL-12 and IL-18 as well as a trend of more anti-inflammatory IFNy in the 2000 µM NAD+ perfusate. In the bronchoalveolar lavage, the pro-inflammatory levels of IL-1α and IL-1β were lower in the 2000 µM NAD+ group. NAD+ administered during EVLP is a promising agent with both anti-inflammatory properties and the ability to improve ischemic lung function.